The Contribution Of Virtual Fitting Room In Fashion Clothing Business: A Systematic Literature Review - Kamilah, Fadilah Haya; Hasya, Afina; Darmastuti, Ismi (InJEBA : International Journal of Economics, Business and Accounting, 2024)
Virtual Fitting Room is the new technologies for trying on clothes without actually trying it. Many studies have conducted research of VFR, but not many conclude the research to help businesses and researchers better understand VFR. The purpose of this systematic literature review is to gather the research journals of VFR and being a guid for future research on knowing more about VFR in the past 5 years. With the selected 20 research journals, this study covers the geographic distribution of VFR research, the method used by researchers and the outcome variables used in VFR research. Our study shows that the majority of research conducted are from USA and china, the method used by most researchers was experiment which have a various outcome, while the most selected key contribution is usage intention’s.